Analisis Persepsi dan Minat Mahasiswa dalam Memutuskan Menjadi Petani Millenial - Nitami, Mayhilda; Maulidar, Maulidar; Susanto, Dimas Bagus; Yani, Rina Novi; Diman, Banta; Musna, Ria Rimfani (Program Studi Agribisnis, Fakultas Pertanian, Universitas Singaperbangsa Karawang, 2024)
The decline in interest among young people today also called millennials is one of the problems faced in realizing sustainable agriculture. The perception of young people towards the profession of a farmer has also become a problem that has resulted in a decrease in the number of farmers in Indonesia. The purpose of this study was to find out what factors influence the perception and interest of students of the Agribusiness Study Program, Faculty of Agriculture, Teuku Umar University in deciding to become millennial farmers; and to find out the relationship between perception and interest of students of the Agribusiness Study Program, Faculty of Agriculture, Teuku Umar University in deciding to become millennial farmers. The study results showed that in external factors, the area of land ownership, parental support, and government support had a low percentage value. While community support and the use of technology had a high percentage value. The correlation between the two variables was 0.511 with a sig.(2-tailed) is 0.001 smaller than the limit of α = 0.05, which means that there is a significant relationship between the two variables of perception and interest of students of the Agribusiness Study Program in deciding to become millennial farmers.